Technological Innovation, Competitiveness and Sustainable Development - Gonel, Feride Doganer (WORLD ASSOC SUSTAINABLE DEVELOPMENT-WASD, SPRU-SCIENCE & TECHNOL POLICY RES, 2008)
Science and Technology (S&T) play a fundamental role in finding solutions to many problems of sustainable development. In the framework of this sustainable technology, technological innovation and sustainable development are very interactive with each other. At the same time, innovations lead to a direct reduction in production costs for companies, therefore companies' competitiveness increases in national and international arena. The purpose of this study is to identify and to present the conditions and situations of technological innovation that foster and promote sustainable development and competitiveness in Turkey. Based on various secondary sources such as activities and annual reports of companies, published articles and deeply interviews and surveys, large companies are investigated for drawing the picture of this sophisticated triangle of technological innovation, competitiveness and sustainable development.
Keywords: Ecological innovation; Competitiveness; Turkey; Sustainable technology; Business & Economics; Public Administration